SETTLING FOR TOLERANCE ON INTERCULTURAL CHILDREN AT SCHOOL: (Case Study on Children aged 5-6 years with Madurese, Makasar and Javanese Ethnics Cultural Background) (International Conference on Elementary Education, 2018)
Tolerance is closely related to mutual respect for others who have different beliefs and forms of behavior. Tolerance is an important character that needs to be developed in the position of cultural ethnic diversity in Indonesia. Each tribe has its own determination to behave in society. Distinguishing one's ethnicity, especially in early childhood, cannot be inferred only from the place of birth, but there are several aspects including the style of language, attitudes, and habits of children in their families. In plain view there are few people who disagree with differences, but if it is not properly understood by children, it will cause a lack of tolerance for themselves, especially at school. Culture is the formation of a child's personality in real world, this is related to the socialization of children who sometimes still choose to be friends. The tolerance in this article looks from the point of view of differences in cultural backgrounds of children aged 5-6 years. Research subjects were children of the Madurese tribe, Makassar tribe, and Javanese tribe. The purpose of this study is to explain the process of settling for tolerance by teachers at school. This research used a qualitative case study approach with data collection techniques namely observation and interview. The results obtained in the process of settling for tolerance at school by teachers through learning activities and habits at school.